The combination of NLR and MEOWS as a potential modality for detecting the severity of preeclampsia: A systematic review - Singgih, Rendy; Kwary, Meilyana Maria Isabela; Tamara, Yosi (Universitas Airlangga, 2023)
HIGHLIGHTS PE is still one of the contributors to morbidity and mortality which is quite high for pregnant women in Indonesia. The use of NLR and MEOWS modalities as predictors of preeclampsia incidence shows significant potential and can be applied especially in facilities with limited resources. ABSTRACT Objective: To describe modalities of detecting the severity of preeclampsia (PE) between neutrophil-to-lymphocyte ratio (NLR) levels and Modified Obstetric Early Warning Systems (MEOWS). Materials and Methods: We used a systematic search in PubMed, ScienceDirect, and Google Scholar for fully-accessed English articles, published between 2015 – 2023 that evaluated modalities between NLR levels and MEOWS for detecting the severity of preeclampsia, which resulted in 208 works of literature. Among the studies, we found 14 literature that met the PICO inclusion criteria and included in this study. Results: PE is still one of the high causes of morbidities and mortality in maternal patients. It is important to predict the possible risk of PE events. NLR is one of the markers that become a prognostic modality to determine the severity of PE. MEOWS is one of the tools to assess the level of care of patients who carry out the treatment. NLR and MEOWS can be modalities for predicting PE severity. Conclusion: NLR and MEOWS can be used even with limited resources. The combined use of NLR and MEOWS can be an alternative and potential modality in detecting PE severity.